Building new twenty-first century medical school libraries from the ground up: challenges, experiences, and lessons learned. - Dexter, Nadine; Muellenbach, Joanne M.; Lorbeer, Elizabeth R.; Rand, Debra; Wilcox, Matthew E.; Long, Bradley A. (Journal of the Medical Library Association, 2019)
The twenty-first century library at a newly opened medical school often differs from those at traditional medical schools. One obvious difference is that the new medical school library tends to be a born-digital library, meaning that the library collection is almost exclusively digital. However, the unique issues related to building a library at a new medical school are not limited to online collections. A unique start-up culture is prevalent, of which newly appointed directors and other library and medical school leaders need to be aware. This special paper provides an overview of best practices experienced in building new medical school libraries from the ground up. The focus is on the key areas faced in a start-up environment, such as budgeting for online collections, space planning, staffing, medical informatics instruction, and library-specific accreditation issues for both allopathic and osteopathic institutions.